EFFECTS OF REPLACING WHEAT OFFAL WITH SUN-DRIED CATTLE RUMEN CONTENTS ON GROWTH PERFORMANCE AND COST BENEFIT OF WEANER RABBITS - Mu'azu, M.S.; Bello, K.M.; Muhammad, A. S.; Egbo, M. L. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study was carried out at the Rabbitry Unit of the Bauchi State College of Agriculture to evaluate the growth performance and cost-benefit of weaner rabbits fed diets containing graded levels of sun-dried cattle rumen contents (SDCRC) as a replacement for wheat offal. Fifty (50) weaner rabbits of mixed breeds were used in an eight-week feeding trial conducted using a completely randomized design. Five dietary treatments were formulated to contain 0 (control), 25, 50, 75, and 100% replacement of wheat offal with SDCRC, while all other dietary components remained constant across treatments. Each treatment had five replicates with two rabbits per replicate. Parameters measured consisted of feed intake, weight gain, feed conversion ratio, and economic indices such as feed cost per kilogram, total feed cost, cost per kilogram weight gain, and cost savings. Results showed no significant (p > 0.05) differences in initial weight, total weight gain, daily weight gain, daily feed intake and feed conversion ratio across the treatment groups, although final weight was significantly affected (p < 0.05), with rabbits on the control diet (0% SDCRC) having the highest final weight (1457.59 g). Total feed intake ranges from 4.04 to 4.19 kg, and feed cost per kilogram diet decreased progressively with increasing SDCRC levels, from ₦95.02 in the control diet to ₦63.45 in the 100% SDCRC diet. Feed cost per kilogram weight gain was lowest in the 100% SDCRC group (₦565.66) compared to the control (₦610.84). A positive cost saving of ₦45.18 was observed in the 100% SDCRC group relative to the control. In conclusion, SDCRC can effectively replace wheat offal in weaner rabbit diets up to 100% without adverse effects on performance while significantly reducing feed costs and improving economic returns.